MsHeresies. - Ehde, Johanna; Gillespie, Diane, F.; Rafstedt, Elisabeth; Rich, Adrienne; Rietlanden Women's office (Amsterdam : Rietlanden Women's Office, 2019)
Woolf, Virginia ; Bell, Vanessa ; Morris, William
feminisme, collectief werk, het ornament
boek